Weathering of Chlorite Illite Deposits in the Hyperarid Qaidam Basin: Implications to Post-Depositional Alteration on Martian Clay Minerals - Sun, Yu; Li, Yiliang; Zhang, Chaoqun; Qin, Xiaorong; Shen, Jianxun; He, Hongping; Pan, Yongxin (Frontiers in Astronomy and Space Sciences, 2022)
Chlorite is the second-most common class of clay minerals on the Martian surface and has been found to coexist with illite in some regions. Although previous studies have paid much attention to the formation of this assemblage, the post-depositional evolution cannot be neglected because the aqueous activities may alter the mineral assemblage and distribution. Here, we report on the post-depositional weathering of lacustrine-fluvial deposits collected from yardangs and dune-covering lake beds in the western Qaidam Basin, one of the largest and highest terrestrial Mars analogs. Mineralogical analysis shows that Fe-clinochlore and illite are the main clay components deposited as detrital particles. Electron microscopic observations of small rusty concretions from yardang deposits revealed that iron was released from clinochlore and formed ferrihydrite in fractures. We suggest that the activities of ephemeral waters after the deposition provide the major source of water that influences the migration of Fe in a long-lasting hyperarid climate. A similar iron-releasing mechanism could have occurred in Nili Fossae on Mars because multiple aqueous activities have shaped the terrains where chlorite illite deposits were identified by orbital near-infrared reflectance spectroscopy. Thus, reconstruction of the aqueous history of ancient Mars from surface minerals requires consideration of post-depositional processes, since groundwater/meteoric water may continuously interact with clay mineral-bearing deposits on Mars after their formation.